DEVELOPMENT OF IPS TEACHING MATERIALS BASED ON LOCAL CULTURE CLASS IV SD 112137 RANTAU UTARA DISTRICTS, LABUHANBATU REGENCY - Dwi Fatmaniati Siregar; Samsidar Tanjung; Hidayat Hidayat (Sensei International Journal of Education and Linguistic, 2021)
This study aims to produce valid local culture-based social studies teaching materials based on the curriculum and local cultural context and to determine the effectiveness of the developed teaching material products. The research subjects were all fourth grade students of SD Negeri 112137 Rantau Utara District. This type of research is (Research & Development). The modified 4-D development model is used, namely: define, plan, develop, and disseminate. Based on the results of the study, it shows that the teaching material products developed are valid by going through several stages of revision / improvement. The percentage of values obtained include (a) language feasibility of 77.88% (b) feasibility of material 78.41% (c) design 76.92%. The effectiveness of teaching materials is based on product trials with two phases, namely, small group evaluations and limited trials. In the small group evaluation phase the percentage was 74% and in the limited trial phase the percentage was 87%. Based on the classical percentage obtained in the first test, it does not meet the proper criteria, namely 85%. Then in the last test, it was obtained a classical percentage of 93.33%, so that it met the completeness criteria and the teaching material product had met the effectiveness indicator.